2024
DOI: 10.1038/s41586-024-07040-9
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur dioxide in the mid-infrared transmission spectrum of WASP-39b

Diana Powell,
Adina D. Feinstein,
Elspeth K. H. Lee
et al.

Abstract: The recent inference of sulfur dioxide (SO2) in the atmosphere of the hot (approximately 1,100 K), Saturn-mass exoplanet WASP-39b from near-infrared JWST observations1–3 suggests that photochemistry is a key process in high-temperature exoplanet atmospheres4. This is because of the low (<1 ppb) abundance of SO2 under thermochemical equilibrium compared with that produced from the photochemistry of H2O and H2S (1–10 ppm)4–9. However, the SO2 inference was made from a single, small molecular feature in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 157 publications
2
16
0
Order By: Relevance
“…Figure 7 shows the comparison between the averaged theoretical transmission spectra generated by EPACRIS and JWST observations of WASP-39 b (Alderson et al 2023;Feinstein et al 2023;Powell et al 2024). The EPACRISpredicted transmission spectra are broadly consistent with the near-and mid-infrared observations.…”
Section: Theoretical Transmission Spectra Of the Atmosphere Of Wasp-3...supporting
confidence: 57%
See 4 more Smart Citations
“…Figure 7 shows the comparison between the averaged theoretical transmission spectra generated by EPACRIS and JWST observations of WASP-39 b (Alderson et al 2023;Feinstein et al 2023;Powell et al 2024). The EPACRISpredicted transmission spectra are broadly consistent with the near-and mid-infrared observations.…”
Section: Theoretical Transmission Spectra Of the Atmosphere Of Wasp-3...supporting
confidence: 57%
“…However, they overpredict the transit depth in the 7-8 μm wavelength range, which corresponds to the dominant SO 2 absorption feature when compared to the MIRI data reported by Powell et al (2024). Consequently, using the same photochemical networks resulted in the lowest χ 2 value of 2.51 when assuming 7.5× solar metallicity, while the χ 2 for 10× solar metallicity was 2.91 (Powell et al 2024). In contrast, the predicted transmission spectra using the photochemical network from the current study showed an even lower χ 2 of 2.10.…”
Section: Theoretical Transmission Spectra Of the Atmosphere Of Wasp-3...mentioning
confidence: 73%
See 3 more Smart Citations